Verb-Verb constructions in the Indo-Portuguese creole of the Malabar - Cardoso, Hugo C. (2015)
South Asian languages are rich in complex-predicate phenomena and, in this domain, vector verbs have received much attention in the literature. Vector verbs are, in fact, often seen to constitute one of the most relevant characteristics of the South Asian Sprachbund (see e.g. Hook 1974; Masica 1975; Abbi & Gopalakrishnan 1991; Abbi 2001; Butt 2003). But while vector verbs are well-established in descriptions of the long-standing languages of the region, their presence in more recent newcomers to the region is less well-known (but see Nordhoff 2012 for Sri Lanka Malay). One of these is Indo-Portuguese, which refers to a string of Portuguese-lexified creoles that formed in coastal South Asia from 1498 onwards and currently subsist in Diu, Daman, Korlai and Kerala (India), and Trincomalee and Batticaloa (Sri Lanka). There is a significant degree of differentiation between the several varieties of Indo-Portuguese, but vector verbs are robust at least in those of the former Malabar [i.e. Kerala], which have Malayalam as their substrate/adstrate. Despite its severe endangerment, Malabar Indo-Portuguese is still spoken in Cannanore and was until recently spoken in Vypeen (Cochin). It is currently in the process of being documented and described.